Model of severe malaria in young mice suggests unique response of CD4 T cells. (4th October 2022) - Smith, Margaret R.; Gbedande, Komi; Johnson, Corey M.; Campbell, Logan A.; Onjiko, Robert S.; Domingo, Nadia D.; Opata, Michael M.
Abstract: Severe malaria occurs most in young children but is poorly understood due to the absence of a developmentally‐equivalent rodent model to study the pathogenesis of the disease. Though functional and quantitative deficiencies in innate response and a biased T helper 1 (Th1) response are reported in newborn pups, there is little information available about this intermediate stage of the adaptive immune system in murine neonates. To fill this gap in knowledge, we have developed a mouse model of severe malaria in young mice using 15‐day old mice (pups) infected with Plasmodium chabaudi . We observe similar parasite growth pattern in pups and adults, with a 60% mortality and a decrease in the growth rate of the surviving young mice. Using a battery of behavioral assays, we observed neurological symptoms in pups that do not occur in infected wildtype adults. CD4 + T cells were activated and differentiated to an effector T cell (Teff) phenotype in both adult and pups. However, there were relatively fewer and less terminally differentiated pup CD4 + Teff than adult Teff. Interestingly, despite less activation, the pup Teff expressed higher T‐bet than adults' cells. These data suggest that Th1 cells are functional in pups during Plasmodium infection but develop slowly.